Applications of isothermal titration calorimetry in pure and applied research from 2016 to 2020. Issue 10 (11th May 2021) - Falconer, Robert J.; Schuur, Boelo; Mittermaier, Anthony K.
Abstract: The last 5 years have seen a series of advances in the application of isothermal titration microcalorimetry (ITC) and interpretation of ITC data. ITC has played an invaluable role in understanding multiprotein complex formation including proteolysis‐targeting chimeras (PROTACS), and mitochondrial autophagy receptor Nix interaction with LC3 and GABARAP. It has also helped elucidate complex allosteric communication in protein complexes like trp RNA‐binding attenuation protein (TRAP) complex. Advances in kinetics analysis have enabled the calculation of kinetic rate constants from pre‐existing ITC data sets. Diverse strategies have also been developed to study enzyme kinetics and enzyme‐inhibitor interactions. ITC has also been applied to study small molecule solvent and solute interactions involved in extraction, separation, and purification applications including liquid‐liquid separation and extractive distillation. Diverse applications of ITC have been developed from the analysis of protein instability at different temperatures, determination of enzyme kinetics in suspensions of living cells to the adsorption of uremic toxins from aqueous streams. Abstract : Advances have been made in the application of isothermal titration microcalorimetry (ITC) and interpretation of ITC data over the last five years. Strategies have been developed to study enzyme kinetics and enzyme‐inhibitor interactions, and analysis has enabled the calculation of kinetic rate constants from pre‐existing ITC data sets. ITC has also been applied to study small molecule solvent and solute interactions involved in extraction, separation, and purification.